Recent advances in the prenatal interrogation of the human fetal genome - Hui, Lisa (Trends Genet, 2012)
The amount of genetic and genomic information obtainable from the human fetus during pregnancy is accelerating at an unprecedented rate. Two themes have dominated recent technological advances in prenatal diagnosis: interrogation of the fetal genome in increasingly high resolution and the development of non-invasive methods of fetal testing using cell-free DNA in maternal plasma. These two areas of advancement have now converged with several recent reports of non-invasive assessment of the entire fetal genome from maternal blood. However, technological progress is outpacing the ability of the healthcare providers and patients to incorporate these new tests into existing clinical care, and further complicates many of the economic and ethical dilemmas in prenatal diagnosis. This review summarizes recent work in this field and discusses the integration of these new technologies into the clinic and society.